Synthesis of Periodic Porous Structures on the Surface of Indium Phosphide - Suchikova, Y.; Kovachov, S.; Konuhova, Marina; Popov, Anatoli I. (Sciendo, 2024)
The paper demonstrates the possibility of forming specific nanostructures of the “parquet” type of nanowires on the InP surface. The resulting nanostructure is characterised by an ordered transverse and longitudinal relative shift of separate nanowires. A dislocation model is proposed that explains the mechanism of such structure formation. The numerical estimates of the geometric parameters of the nanostructure obtained during theoretical modelling are quite adequate for the experimental results. © 2024 Sciendo. All rights reserved. --//-- This is an open-access article Y. Suchikova and S. Kovachov and I. Bohdanov and M. Konuhova and A. I. Popov, Synthesis of Periodic Porous Structures on the Surface of Indium Phosphide, Latvian Journal of Physics and Technical Sciences, 2024, Volume 61, Issue 5, doi:10.2478/lpts-2024-0032 published under the CC BY-NC-ND 4.0 licence.
The study has been supported by the Ministry of Education and Science of Ukraine via Project No. 0122U000129 “The Search for Optimal Conditions for Nanostructure Synthesis on the Surface of A3B5, A2B6 Semiconductors and Silicon for Photonics and Solar Energy”. In addition, the research of A.I.P. and Y.S. has been partly supported by COST Action CA20129 “Multiscale Irradiation and Chemistry Driven Processes and Related Technologies” (MultiChem). Furthermore, A.I.P. also thanks HORIZON 2020 RISERADON Project “Irradiation Driven Nanofabrication: Computational Modelling Versus Experiment” for partial support. Institute of Solid-State Physics, University of Latvia as the Centre of Excellence has received funding from the European Union’s Horizon 2020 Framework Program H2020-WIDESPREAD-01–- 2016–2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Dislocations; electrochemical etching; indium phosphide; periodic nanostructures; porous oxide